Prototype of humidity and temperature control system in IoT-based coffee drying process - T, Alan; Zahri, Dizi Eltrien; Handayani, Marta Tika (Sriwijaya Electrical and Computer Engineering Journal, 2024)
Drying coffee beans plays an important role in determining the final quality of the coffee beans. Drying is usually done traditionally by drying in the sun. This drying has many shortcomings, so a prototype of an IoT-based humidity and temperature control system for the coffee drying process was created. The sensors and microcontroller are DHT11 and ESP32, respectively. This prototype will work only if the sensed temperature is higher than 60 oC and the drying room’s humidity reaches 12% then the control system will activate a fan. The temperature and humidity display will be displayed on the LCD layer of the prototype. Data regarding the temperature and humidity in the room will be sent to Blynk (a free phone application commercially available), so that the users can see and control these variables from their cell phone.. In this way, users can control and know the temperature and humidity during the coffee bean drying process.